Pathological observations of Ficus tsiela (Rox b) toxicity in rats - Litty Mathew (Centre for Excellence in Pathology, College of Veterinary and Animal Sciences, 2009)
The present study entitled ‘Pathological Observations of Ficus tsiela (Rox b) Toxicity in rats’ was undertaken by administering the animals with different concentrations of fresh juice and alcoholic extract for a period of 21 days. The weekly body weights, clinical signs, haematology, biochemical parameters, gross pathology and histopathology of various organs were analysed to study the effect. Phytochemical evaluation of the fresh juice and extract was done and the oxidative damage of the liver was assessed by the estimation of lipid peroxides and reduced glutathione.